A set of specific miRNAs is connected with murine and human gastric cancer. Issue 3 (2nd November 2012) - Shah, Aftab Ali; Leidinger, Petra; Backes, Christina; Keller, Andreas; Karpinski, Pawel; Sasiadek, Maria M.; Blin, Nikolaus; Meese, Eckart
Abstract MircoRNAs as a new class of regulatory molecules have been investigated in many specific cells and organs in healthy and diseased conditions. Although miRNA signatures can be directly assessed in patients' affected tissues such as tumor sections, recent studies revealed that miRNA profiles can also be obtained indirectly, that is, from the patients' peripheral blood. For better understanding of miRNA's contribution to gastric carcinoma (one of the leading causes of cancer‐related mortality worldwide), we screened for deregulated miRNAs in blood collected from human cancer patients and compared the expression patterns with a gastric carcinoma mouse model (Tff1 knock‐out). The profiles were assessed using species‐specific miRNA microarrays. Among many dozens of deregulated miRNAs (219 in H. sapiens; 75 in M. musculus), a subset of eight miRNAs comparable in sequence from both species was noted. By in silico analysis, their involvement in targeting neoplastic and MAPkinase pathways was demonstrated. We found a high probability of linkage of all noted miRNAs to pathways in cancer with P‐values of 0.013 and 0.018 in mice and humans, respectively. Linkage to the MAPK‐signaling pathway in mice was observed with a P‐value of 0.01. Moreover, when comparing the 219 deregulated miRNAs obtained from blood with deregulated miRNAs derived from gastric cancer (GC) tissues, as published previously, 24 miRNAs were identical. If confirmed in a larger patient pool, these miRNAs could constitute appropriate blood‐born biomarkers for GC. © 2012 Wiley Periodicals, Inc.